2019
DOI: 10.1101/19009431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of polygenic risk scores for coronary artery disease with subsequent events amongst established cases

Abstract: Background: There is growing evidence that polygenic risk scores (PRS) can be used to identify individuals at high lifetime risk of coronary artery disease (CAD).Whether they can also be used to stratify risk of subsequent events among those surviving a first CAD event remains uncertain.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…However, restricting prognostic study samples to individuals with cancer can cause "collider bias", which can potentially induce an attenuation, reversal or overestimation of associations between otherwise independent exposures for cancer progression when adjusting or selecting for a common consequence of those two exposures [124][125][126]. When restricting the study sample to those who have cancer in prognostic studies, all independent risk factors for cancer incidence become associated with each other.…”
Section: Evaluating Risk Factors For Cancer Progression and The Poten...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, restricting prognostic study samples to individuals with cancer can cause "collider bias", which can potentially induce an attenuation, reversal or overestimation of associations between otherwise independent exposures for cancer progression when adjusting or selecting for a common consequence of those two exposures [124][125][126]. When restricting the study sample to those who have cancer in prognostic studies, all independent risk factors for cancer incidence become associated with each other.…”
Section: Evaluating Risk Factors For Cancer Progression and The Poten...mentioning
confidence: 99%
“…Conditioning analyses on colorectal cancer incidence (i.e., case status, a collider in this scenario) could generate a spurious association between two causes of colorectal cancer incidence (i.e., body mass index and cigarette smoking). This then induces an association between body mass index and colorectal cancer survival (via cigarette smoking) even in the absence of a true causal relationship between these two traits in the target population genetic effects of cancer incidence to eliminate (when the genetic effects on disease incidence and progression are independent) or, more realistically, reduce this bias [126,130,131].…”
Section: Evaluating Risk Factors For Cancer Progression and The Poten...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, restricting prognostic study samples to individuals with cancer can cause "collider bias", which can potentially induce an attenuation, reversal or overestimation of associations between otherwise independent exposures for cancer progression when adjusting or selecting for a common consequence of those two exposures [124][125][126]. When restricting the study sample to those who have cancer in prognostic studies, all independent risk factors for cancer incidence become associated with each other.…”
Section: Evaluating Risk Factors For Cancer Progression and The Poten...mentioning
confidence: 99%
“…Indeed, a study investigating the association of known common type 2 diabetes variants with BMI (a strong risk factor for type 2 diabetes) found three overestimated and one underestimated associations among 11 type 2 diabetes risk alleles when comparing to a non-diabetic population (16). Another example uses a polygenic risk score to examine associations between CHD genetic risk variants and cardiovascular outcomes and found that these differ when examined in those with and without prior CHD (18). These studies highlight the need to address this bias by detecting and accounting for its presence in caseonly studies.…”
Section: Introductionmentioning
confidence: 99%